How School Culture and Climate Mediated Student’s Mathematics Achievement: A Path Analysis of PISA 2022 Indonesia Data - Latifah, Ayustina Intan; Kismiantini, Kismiantini (Jurnal Pendidikan Progresif, 2025)
How School Culture and Climate Mediated Student’s Mathematics Achievement: a Path Analysis of PISA 2022 Indonesia Data. Indonesia’s declining mathematics performance in PISA 2022 highlights the need to examine key educational factors affecting student achievement. In the post-pandemic context, school culture and climate have become increasingly important in shaping learning outcomes. This study investigates how these factors mediate the effects of teacher support, gender, and socioeconomic and cultural status (ESCS) on students’ mathematics achievement. Objectives: This study aims to: (1) examine the effects of teacher support, gender, and socioeconomic and cultural status on school climate and culture indicators (bullying victimization, sense of belonging, feeling safe, and school safety risks); (2) assess the influence of these indicators on students’ mathematics achievement; (3) analyze the direct effects of the independent variables on mathematics achievement; and (4) evaluate the mediating role of school climate and culture in these relationships. Methods: This quantitative study used cross-sectional data from the PISA 2022 Indonesia dataset, comprising 12,491 students from 410 schools. Data were analyzed using a parallel multiple mediation model with path analysis, employing Maximum Likelihood estimation and nonparametric bootstraping with 1,000 replications. Findings: The results showed that all independent variables significantly affected all four indicators of school culture and climate. Bullying victimization, lack of feeling safe, and school safety risks had significant negative effects on math achievement, while a sense of school belonging had a significant positive effect. Teacher support and gender had significant negative effects on mathematics achievement, while socioeconomic and cultural status had significant positive effects. All mediating variables significantly mediated the relationships between the independent variables and math achievement. Conclusion: Interventions to improve math achievement should not rely solely on direct teacher support, but also prioritize building a positive school climate by strengthening students’ sense of belonging and reducing bullying as these are critical pathways influencing academic success. Keywords: PISA 2022, mathematics achievement, path analysis, mediation model.